2021
DOI: 10.20511/pyr2021.v9nspe2.1087
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effect of internet addiction on the tendency to marital infidelity in couples in Shiraz

Abstract: Background and Purpose: The purpose of this study was to investigate the effect of Internet addiction on the tendency to marital infidelity in couples in Shiraz. Method: The statistical population includes all men and women who referred to counseling centers in Shiraz for marriage counseling in 2015. These people completed the Internet Addiction Questionnaire and were divided into two groups: Internet addicts and normal. Samples were selected by available sampling method from Shiraz city counseling centers, 60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The factors include the items that influence the marital relationships and are considered as taboo in our society. Considering the fact that romantic relationships have the tendency to have high levels of both sexual frequency and relationship satisfaction in the beginning of relationships (Gonzalez-Rivera et al, 2019) which is also found in several studies about the positive relationship between them (Baboo & Mohammadi, 2021).…”
mentioning
confidence: 84%
“…The factors include the items that influence the marital relationships and are considered as taboo in our society. Considering the fact that romantic relationships have the tendency to have high levels of both sexual frequency and relationship satisfaction in the beginning of relationships (Gonzalez-Rivera et al, 2019) which is also found in several studies about the positive relationship between them (Baboo & Mohammadi, 2021).…”
mentioning
confidence: 84%
“……it affected…my roles as a husband and as a father to my children…it affected me in that depth…it affected my children as well because they were used to having me every weekend and then now…suddenly your father is no longer coming home every weekend now, he's coming once a month…he's at times full of excuses… Participant D also related how his family life was affected: …also affected our kids in one way or another because they could see that there was something wrong… Kioko (2015) noted that marital infidelity leads to disintegration of the family unit, which in turn results in poor, physical, mental and moral growth among the family members. It threatens the family structure and consequently the feeling of marital belonging (Baboo & Mohammadi, 2021). Ojedokun (2015) indicated that an extramarital affair has a great negative impact on home stability.…”
Section: Overview Of the Themes And Sub-themesmentioning
confidence: 99%
“…Virtual social networks can transform cultural, social, and personal lives, values, and attitudes [25]. According to Iranian literature, the influence of virtual social networks has had a significant positive impact on how people view marriage, extramarital relationships, and the propensity for infidelity in relationships [26,27].…”
Section: Introductionmentioning
confidence: 99%